PERANCANGAN APLIKASI PERHITUNGAN ZAKAT MAL, MENENTUKAN WAKTU SHALAT DAN ARAH KIBLAT MENGGUNAKAN GPS BERBASIS ANDROID - Yasmin Dara; Denny Kurniadi; Khairi Budayawan (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2014)
The daily prayers are an important thing that should be done by every moslem in this world. One of the priorities in praying is to pray on the right time with directed to mecca  Nowadays, most of moslem tend to neglect the time to pray as they are busy of their works. At this time, a moslem have to be discipline in splitting  the  time  to  do  shalat.  Those who  earn  and  have enough income  is supposed to pay the Zakat Mal according to the amount of their income. In this modern era, handphone has been used by the people in facilitating their works in daily life, because handphone have many functions out of its main function. Android is an operation system that is inserted into handphone which has function to help the user in installing the application that they need. In this final project, the writer proposed a title “The designing of application in calculating Zakat Mal, Determining the Time of Shalat, and Direction to Mecca by using GPS with android system base. This application will remind the user of the time of shalat and  show  the  direction  to  Mecca  that  is  supported  by  GPS  system.  This application also includes the menu for calculating the Zakat Mal.   Keywords:  Android Application, Zakat Mal, Shalat time, Direction of Kiblat. GPS (Global Position System)